International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2006. SPEEDAM 2006.
DOI: 10.1109/speedam.2006.1649759
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of ZigBee technology to electric motor rotor measurements

Abstract: The purpose of this work is to determine the applicability of the ZigBee technology to electric motor rotor measurements. Requirements for data transmission, electrical structure and powering of a sensor are discussed. A prototype wireless ZigBee-based torque sensor is built and tested. The results of the tests are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…If the symbol duration is much less than T c , the channel is considered as being stationary in practice. With a worst case f D ≈112 Hz, T c ≈8.9 msec, much larger than the chip duration 1 μsec and the DSSS symbol duration 32 μsec, suggesting that the Doppler effect is insignificant, as was similarly reasoned in [4].…”
Section: Channel Coherence Timementioning
confidence: 64%
See 2 more Smart Citations
“…If the symbol duration is much less than T c , the channel is considered as being stationary in practice. With a worst case f D ≈112 Hz, T c ≈8.9 msec, much larger than the chip duration 1 μsec and the DSSS symbol duration 32 μsec, suggesting that the Doppler effect is insignificant, as was similarly reasoned in [4].…”
Section: Channel Coherence Timementioning
confidence: 64%
“…Both studies did not mention transmission errors in their experiments. In [4], an IEEE 802.15.4-compatible wireless torque sensor was mounted on an electric motor spindle; its communication performance was measured by sending a series of 2-byte probe packets and counting the number of received probes at radial rotation speeds of 1.26 to 6.28 m/s. Very few packets were lost, and the paper concluded that the rotation induced no significant communication errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wireless sensors are promising for replacing cables in monitoring systems and enabling flexible sensing over structures that are difficult to monitor with wired sensors. Rotating mechanical structures found in a wide range of mechanical, civil and vehicular systems are among such hard-to-reach structures with crucial monitoring importance (Miettien et al, 2002;Varghese et al, 2002;Dzapo et al, 2004;Sarkimaki et al, 2006). Such structures are often found in metallic enclosures that create harsh radio propagation conditions, causing frequent communication errors, low data throughput, unknown system reliability and performance variation dependent on sensor placement strategies (Sundararajan et al, 2005;Werb et al, 2005, Ota andWright, 2006;Tang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the IEEE802.15.4 standard [1] , ZigBee wireless technology just fulfills the requirements, which is suited to industrial sensor networks for auto-control, security and intelligent home appliances [2][3][4][5][6][7] . For wider applications, the chip cost and power consumption must be drastically reduced [8,9] , the chip integrated into a small chip area with a low cost technology, as standard CMOS technology.…”
Section: Introductionmentioning
confidence: 99%